Cerebral hemorrhage in severe preeclampsia: case series - Lacunza-Paredes, Rommel (2017)
Cerebral hemorrhage is a rare event but with devastating consequences. Severe preeclampsia in pregnant women is the most frequent cause of cerebral hemorrhage in the puerperium. Four cases of cerebral hemorrhage in severe preeclampsia are presented and the various factors conditioning its appearance are analyzed. The literature is reviewed.